Educational microenvironment at the classical university - R. M. Kumysheva (Moscow Polytechnic University, 2022)
The article contains the structural and functional analysis of the educational microenvironment at the university. By the example of the medical faculty there is shown its role in the transformation of students' educational activities into their living space and real practice.